CALCULATION OF LINEAR FRACTIONAL FUZZY TRANSPORTATION PROBLEM USING SIMPLEX METHOD - Behera, S. P.; Pati, J. K.; Raut, P. K.; Mahanta, Kamal Lochan (International Journal of Engineering Science Technologies, 2022)
In this research article, we implement a methodology for solving fuzzy transportation problems involving linear fractional fuzzy numbers. The main aim of this paper is to find optimum values of the fuzzy transportation problems by simplex method with the help of a triangular fuzzy number (TFN) as the costs of objective function. The outcome of this method is explained with a numerical example.